Teaching ESL/EFL reading and writing - Nation, I. S. P. (ESL & applied linguistics professional series, 2009)
Using a framework based on principles of teaching and learning, this guide for teachers and teacher trainees offers suggestions for helping learners at various levels of proficiency develop their reading and writing skills and fluency.